1971
DOI: 10.1104/pp.47.6.745
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sterol Composition during Greening of Etiolated Barley Shoots

Abstract: The following sterols were identified in barley shoots: stigmasterol, 8-sitosterol, campesterol, and cholesterol. The total sterol content of green and etiolated tissue was 2.84 and 3.20 milligrams per gram dry weight, respectively. The free sterols accounted for most of the difference in total sterol content. The sterol ester, sterol glycoside, and acylated sterol glycoside contents of green and etiolated barley shoots were essentially the same. Etiolated tissue had twice as much total 8-sitosterol as stigmas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
25
3

Year Published

1971
1971
1987
1987

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 15 publications
5
25
3
Order By: Relevance
“…Furthermore, it has been reported that the steryl ester composition of greening barley shoots was quite different from the free sterols (1). However, in this same study the steryl glycosides were very similar in composition to the free sterols, making this sterol form the more likely for translocation.…”
supporting
confidence: 44%
“…Furthermore, it has been reported that the steryl ester composition of greening barley shoots was quite different from the free sterols (1). However, in this same study the steryl glycosides were very similar in composition to the free sterols, making this sterol form the more likely for translocation.…”
supporting
confidence: 44%
“…This higher sterol content in mature tobacco and in Solanum andigena leaves was mainly due to an increase in free sterols (1,15), whereas, in Solanum tuberosum, glycosidic sterols accounted for most of the increase (10). In the experiment presented here, the free sterols are the dominant form and this agrees with other authors (6,15,25) and our own previous work (26) with other plant leaves. During this experiment, however, this fraction did not show an increase with plant age.…”
Section: Resultssupporting
confidence: 94%
“…In the experiment presented here, the amounts of esterified and glycosidic sterols are lower than those observed by Bush et al (6) in barley shoots and by Grunwald (15,16) in tobacco leaves. In tobacco, the steryl esters decreased slightly with plant age and the quantities of esterified and glycosidic sterols were of the same magnitude (15).…”
Section: Resultscontrasting
confidence: 75%
See 2 more Smart Citations